Impact of LVAD Implantation Site on Ventricular Blood Stagnation - Prisco, Anthony R. (ASAIO J, 2017)
Treatment of end-stage heart failure includes cardiac transplantation or ventricular assist device (VAD) therapy. While increasingly prevalent, current VAD therapy has inherent complications, including thrombosis. Studies have demonstrated that VAD implantation alters intra-cardiac blood flow, creating areas of stagnation that predispose to thrombus formation. Two potential surgical configurations exist for VAD implantation: through the apical or diaphragmatic surfaces of the heart. We hypothesized that diaphragmatic implantation causes more stagnation than apical implantation. We also hypothesized that intermittent aortic valve (AV) opening reduces stagnation of blood inside the left ventricle (LV) when compared to a closed AV. To test these hypotheses, a human left-ventricle geometry was re-created in silico and a VAD inflow cannula was virtually implanted in each configuration. A computational indicator-dilution study was conducted where “virtually-dyed blood” was washed out of the LV by injecting blood with no dye. Simulations demonstrated a substantial reduction in stagnation with intermittent AV opening. In addition, virtual dye was cleared slightly faster in the apical configuration. Simulations from our study demonstrate the clinical importance of VAD management to allow intermittent opening of the AV to prevent subvalvular stagnation, and it also suggests that apical configuration might be more hemodynamically favorable.